Pelatihan Kader Dalam Penggunaan Buku KIA Sebagai Upaya Peningkatan Pengetahuan Kesehatan Ibu Hamil - Rosalinna Rosalinna; KH Endah Widhi Astuti (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: Efforts to prevent complications both during pregnancy and labor can be made as early as possible through early detection. This early detection will work well if there is active participation from cadres in mentoring pregnant women themselves and their families. Efforts to improve human resources through training on the use of the MCH Handbook for cadres. One person died as a result of severe pre-eclampsia, and another died as a result of pleural effusion disease. Methods: The method is to empower the community, especially cadres, in the use of the MCH Handbook as an effort to increase knowledge of pregnant women's health for the continuity of the implementation of assistance for pregnant women in collaboration with the Village Midwife, Jaten. The number of participants was 30. The instrument used was a knowledge questionnaire. Results: The obtained health education skills using the MCH handbook for pregnant women by cadres in Jetis Village before the activity was 35.20 (1.51), and it was 89.81 (0.63) after community service activities. Statistical test results show a p-value = 0.000, which means that there is a significant. Conclusion: The effect of cadre training in the use of MCH handbooks as an effort to increase maternal health knowledge is successfully achieved. This service can be passed on to the wider community.